PENGEMBANGAN TES HIGHER ORDER THINKING SKILL (HOTS) PADA MATERI GETARAN HARMONIS UNTUK SMA - Hidayah, Nurul; Maria Silitonga, Haratua Tiur; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research  aims to assess the advisability of higher order thinking skill (HOTS) test of Physics for senior high school students. Specifically, this reseach was conducted to find out the characteristic of the HOTS test and to define the oppropriateprecentage of the test which is based  on the students’ responses. The metode used in this research is Research and Development (R & D). The method uses the stages which was developed by Borg and Gall which have been simplified. The HOTS test is developed basd on the Taxonomy Bloom which has been revised. It consists of 10 test points that have been validated by five physics experts. The experiment was done to 104 XI students from three different schools. The result of the experiment shows that from 10 test points, all of the items are highly correlated as the construct validity with analysis factor test by using SPSS, the level of contents of validity with the mean score 0.737. The validity of the items shows that all of the test items are valid based on SPSS application. The realibility of test items is 0.7, the index of difficulty of the test starts from 0.02 until 0.55, and  the level of legibility is 0.66 which mean all of the items are categorised as good test items. The students’ reponses from the questionnaires result positive with 79.6% for the mean score. Based on these characteristics, the HOTS test can be used to measure the higher order thinking skill of physics for senior high school students. Keywords: test development, HOTS, Harmonic Vibration